Greenhouse gas emissions vs CO2 emissions: Comparative analysis of a global carbon tax. (15th September 2021) - Nong, Duy; Simshauser, Paul; Nguyen, Duong Binh
Highlights: A world carbon tax policy is examined with/without inclusion of non-CO2 emissions. The impacts are highly divergent with/without inclusion of non-CO2 emissions. The divergences become larger along with increased costs to economies. Developing nations experience relatively high economic contractions. Major polluting nations (China, USA, India, and Russia) have low marginal abatement costs. Abstract: Both CO2 and non-CO2 emissions are liable in climate change policies in many countries around the world. However, there are still many impact assessment studies in different regions that consider only CO2 emissions. We hypothesise that excluding non-CO2 greenhouse gas emissions, which are also liable in climate change policies, may lead to misleading results and impacts. We employ a global climate change policy model (GTAP-E-PowerS) to examine how the impact of a uniform carbon tax at US$15 applying to the world regions are different when only CO2 emissions are liable compared to the case that non-CO2 emissions are additionally subject to the tax. That is, the impacts of the carbon tax applying to CO2 emissions only (against no carbon tax) will be compared to the impacts of such a tax applying to both CO2 and non-CO2 greenhouse gas emissions (against no carbon tax). Results show the deviations in the impacts between with and without inclusion of non-CO2 emissions are more obvious in developing countries particularly by comparison to developed nations. Iran, for instance, experiences a higher reduction in real GDP of 1.52 percentage points when non-CO2 emissions are overlooked. These impact deviations also rise with increased costs to economies (e.g., more sectors involved or higher tax rates). We find developing countries experience higher contraction rates in their economies than developed nations. Iran, Kazakhstan, South Africa, China, India, Russia, Mexico, and Indonesia all experience 2–5.1% reductions in real GDP relative to business-as-usual (no carbon tax), while such reductions are below 0.8% in Australia, the United States and other developed nations because emission costs compared to economy size are relatively high in developing nations. Major polluting countries like China, the United States, India, and Russia were also found to have low marginal abatement costs compared to other nations due to high emission levels and input substitution possibilities. To provide more accurate and insightful impacts of climate change policies, we recommend future studies include both CO2 and non-CO2 emissions in models.